2009
DOI: 10.1080/10401330902791321
|View full text |Cite
|
Sign up to set email alerts
|

Personal Digital Assistants: A Review of Current and Potential Utilization Among Medical Residents

Abstract: PDAs are perceived as a valuable resource by most medical residents. Further studies are necessary to confirm that daily PDA use by housestaff confers an educational, institutional, and patient care benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…18 Similarly, Tempelholf's 2009 systematic review on PDA use among medical residents indicated that 90% of residents with PDAs used them to access drug information resources daily, 50% accessed electronic medical textbooks and clinical decision support systems daily, and 20-30% used them daily for patient care tasks such as retrieving laboratory values and tracking patients. 19 Smartphones and PDAs may also be used in more formal educational contexts within the clinical realm. For instance, Ho and colleagues at the University of British Columbia studied the use of PDAs to record case logs, medical students' mechanism for keeping track of the clinical cases they see within their clerkship experience, and communicating their learning portfolios to faculty.…”
Section: Use Of Smartphones In Instruction and Educationmentioning
confidence: 99%
“…18 Similarly, Tempelholf's 2009 systematic review on PDA use among medical residents indicated that 90% of residents with PDAs used them to access drug information resources daily, 50% accessed electronic medical textbooks and clinical decision support systems daily, and 20-30% used them daily for patient care tasks such as retrieving laboratory values and tracking patients. 19 Smartphones and PDAs may also be used in more formal educational contexts within the clinical realm. For instance, Ho and colleagues at the University of British Columbia studied the use of PDAs to record case logs, medical students' mechanism for keeping track of the clinical cases they see within their clerkship experience, and communicating their learning portfolios to faculty.…”
Section: Use Of Smartphones In Instruction and Educationmentioning
confidence: 99%
“…Use was approximately 60% in 2001 and as high as 70% in 2007, with up to 30% of residency programs actually requiring their residents to use a handheld computing device as a part of their training. 8 With the advent of smartphones, not only have the capabilities afforded to users increased dramatically but so has the percentage of physicians using them, estimated to be as high as 90% of physicians by 2012. 9 Doctors increasingly rely on e-mail communication rather than verbal communication and their mobile phones rather than their pagers.…”
Section: Introductionmentioning
confidence: 99%
“…10 This has been documented to provide significant financial benefit to academic hospitals. 8 In addition to improving efficiency in communication and access to information, portable electronic devices have successfully been shown to facilitate diagnosis and treatment via "teleconsultation" [10][11][12][13] and have the potential to decrease surgical errors. 14 This pilot study surveyed the residents in of one of the largest Departments of Surgery in North America to assess their use of the Internet, e-mail, and personal electronics in day-today practice and their knowledge of hospital policies regarding the use of these technologies, as well as their current and preferred methods of communicating with other members of the surgical team.…”
Section: Introductionmentioning
confidence: 99%
“…As technology has advanced, portable handheld devices are now available that allow an individual the ability to review information at the point of need. These devices are already being used for patient care, and their uses have been described previously (69). …”
mentioning
confidence: 99%